A recursive and reflective peregrination: The essence of becoming a teacher leader - Hibanada, Rowena R. (Animo Repository, 2017)
This qualitative study explored the lived experiences of International Leaders in Education Program (ILEP) teacher fellows. This study is grounded on the tradition of Hermeneutic phenomenology using van Manens (1990) framework . The aim of this study is to reveal the essence of becoming a teacher leaders according to the six participants representing International Leaders in Education Program (ILEP) Teacher-fellow cohorts from years 2013-2015. They are teaching in public or private secondary schools in the Philippines and were purposely selected to provide substantial responses from their rich experiences in becoming teacher leaders. In allowing the voices of ILEP teacher fellows in this study, responses from the semi-structured interviews were coded to extract narratives where recurrent themes and subthemes were identified. The emergent core themes comprised the key findings supported by the relevant research literature on teacher leadership. Core themes identified in this study are (theme 1.0) A Teacher leaders leads from the classroom but extends beyond usual school duties (theme 2.0 ) critical reflection is an integral part of becoming a teacher leader (theme 3.0) authentic learning experiences allow teacher leaders to make meaningful connections (theme 4.0) personal, social and professional contexts impact teacher leadership (theme 5.0) teacher leadership is a growth process and a peregrination of continuous learning There are five important elements in teacher leadership growth process: establishing credibility through expertise, collaborating with others, empowerment, engaging others and expanding opportunities for leadership (theme 6.0) becoming a teacher leader is a reflective and recursive peregrination. Hence, self-motivation guided by passion and purpose of the teacher is the fire that sustains teachers in a reflective and recursive peregrination of becoming a teacher leader. Recommendations from this research include: recognizing the value of teacher leadership within the school context and the whole educational system, supporting the development of teacher leadership, advocating teacher leadership and encouraging teachers to assume teacher leader roles for students achievement, engaging teachers and school leaders in professional learning community, and providing professional development opportunities for teachers and school leaders about teacher leadership.